2018
DOI: 10.4314/ijs.v20i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hydatidosis and fertility of hydatid cyst in slaughtered camels in Maiduguri, Nigeria

Abstract: The study was conducted to determine the presence of hydatid cyst disease in slaughtered camels at the Maiduguri metropolitan abattoir. Four hundred and four (404) camels (162 males and 242 females) were examined at post mortem by visual inspection and palpation for evidence of cystic hydatidosis and fertility of the cyst. The prevalence was determined based on the sex and location of the cyst. An overall prevalence of 7 (1.73%) was recorded. Based on sex, 2 (1.20%) and 5 (2.10%) were found for males and femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…Previous studies have reported similar results implicating camels as most susceptible. In some areas, prevalence has been found to reach as high as 70% in camels and 40% in other livestock [18, 35, 36], although lower prevalence has also been documented in other locations [37, 38]. The high fertility rate observed in camels suggests that they play a significant epidemiological role in the transmission of CE in Nigeria, especially in the North-West and North-East zones.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported similar results implicating camels as most susceptible. In some areas, prevalence has been found to reach as high as 70% in camels and 40% in other livestock [18, 35, 36], although lower prevalence has also been documented in other locations [37, 38]. The high fertility rate observed in camels suggests that they play a significant epidemiological role in the transmission of CE in Nigeria, especially in the North-West and North-East zones.…”
Section: Discussionmentioning
confidence: 99%
“…In the North, between 55.5 and 70.9% have been reported in some states during the 1970-1980s [25,29], while recent surveys within the last decade put CE prevalence between 8.97 and 59.3% in camels being higher than other concurrently examined livestock [48,49,58,59]. In few northern states, infection in camels could be very low as reported in Maiduguri, Borno state where a prevalence of 1.73% (mainly fertile cysts) was found among 404 camels examined postmortem [42]. To date, this variation in infection rates among livestock across the country specifically in states where surveys have been conducted (Fig.…”
Section: Prevalence In Animalsmentioning
confidence: 96%
“…For example, camels are often slaughtered after 8-10 years of age, leading to increased exposure and subsequent risk of acquiring the infection [59]. Recently, differences in ambient temperatures across the country were suggested as a possible factor that could cause prevalence to vary as some states experience temperatures as high as 45 °C resulting in desiccation of eggs [42]. Furthermore, since no study has been dedicated to identifying local factors responsible for human and livestock CE in Nigeria, the need for such studies to identify local transmission patterns cannot be overstated.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Hydatid cysts are usually identified during the slaughter of domestic animals at slaughterhouses. However, serological methods have been used to diagnose hydatidosis in domestic animals (Dada and Belino, 1978;Dada et al, 1981;Haroun et al, 2008;Sazmand et al, 2013;Igwenagu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The most reliable diagnostic technique is cyst detection during meat inspection or at post-mortem examination via visualization and palpation for dead animals. However, with regard to the living animals, serology and ultrasonography are the diagnostic methods of choice (Dada and Belino, 1978;Igwenagu et al, 2018). Therefore, serological methods are highly valuable and useful for monitoring and controlling hydatid disease in camels.…”
mentioning
confidence: 99%